Androgen Regulation of 5α-Reductase Isoenzymes in Prostate Cancer: Implications for Prostate Cancer Prevention - Li, Jin; Ding, Zhiyong; Wang, Zhengxin; Lu, Jing-Fang; Maity, Sankar N.; Navone, Nora M.; Logothetis, Christopher J.; Mills, Gordon B.; Kim, Jeri (PLOS ONE, 2011)
The enzyme 5α-reductase, which converts testosterone to dihydrotestosterone (DHT), performs key functions in the androgen receptor (AR) signaling pathway. The three isoenzymes of 5α-reductase identified to date are encoded by different genes: SRD5A1, SRD5A2, and SRD5A3. In this study, we investigated mechanisms underlying androgen regulation of 5α-reductase isoenzyme expression in human prostate cells. We found that androgen regulates the mRNA level of 5α-reductase isoenzymes in a cell type–specific manner, that such regulation occurs at the transcriptional level, and that AR is necessary for this regulation. In addition, our results suggest that AR is recruited to a negative androgen response element (nARE) on the promoter of SRD5A3 in vivo and directly binds to the nARE in vitro. The different expression levels of 5α-reductase isoenzymes may confer response or resistance to 5α-reductase inhibitors and thus may have importance in prostate cancer prevention.